Pengaruh Perkembangan Ekonomi Digital Terhadap Perusahaan Start-Up di Indonesia - Ade Andani; Erine Novianta; Adhe Friam Budhi; Adek Arya; Zalika Sabina; Wahyu Indah Sari (Jurnal Kajian dan Penelitian Umum, 2024)
The development of the digital economy has brought significant changes in various aspects of life, including in the business world. Digital transformation has turned Indonesia into one of the countries with the largest growth in startups and e-commerce along with the increase in smartphone use and internet telecommunication infrastructure, provides a great opportunity for startups companies to be able to develop their business by utilizing digital marketing. The aim of the research is to determine the influence of the development of startups companies caused by economics, digitalization and online marketing. This research uses quantitative methods with multiple linear regression analysis techniques, the data used is secondary data. The result of this research shows that the development of the digital economy and digital marketing has an influence on the development of startup companies in Indonesia. Because it is easier for startup companies to reach a wide range of customers so their business will grow quickly.